2011
DOI: 10.1016/j.optcom.2011.04.059
|View full text |Cite
|
Sign up to set email alerts
|

High dynamic range imaging method for interferometry

Abstract: We demonstrate a method to easily and quickly extend the dynamic range imaging capabilities of the camera in a typical interferometric approach. The camera dynamic range is usually low and limited to 256 gray levels. Also, it is well known that one may have over or under-exposed regions in the interferogram (due to nonuniform illumination) which makes these image regions not reliable. In our proposed method it is not necessary to obtain or use the non-linear camera response curve in order to extend the camera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The common link between all these approaches is the use of the spiral phase transform, which is used to factorise cryo-EM maps into amplitude and phase terms in real space for different resolutions. The spiral phase transform has been extensively used in optics for phase extraction in interferometry 35 39 or by Shack-Hartmann sensors 40 , 41 . This transformation is not new in cryo-EM as it has been proposed previously to facilitate particle screening 42 , CTF estimation 43 and local and directional resolution determination 34 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The common link between all these approaches is the use of the spiral phase transform, which is used to factorise cryo-EM maps into amplitude and phase terms in real space for different resolutions. The spiral phase transform has been extensively used in optics for phase extraction in interferometry 35 39 or by Shack-Hartmann sensors 40 , 41 . This transformation is not new in cryo-EM as it has been proposed previously to facilitate particle screening 42 , CTF estimation 43 and local and directional resolution determination 34 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The common link between all these approaches is the use of the spiral phase transform, which is used to factorize cryo-EM maps into amplitude and phase terms in real space for different resolutions. The spiral phase transform has been extensively used in optics for phase extraction in interferometry (Larkin, Bone et al 2001, Antonio Quiroga and Servin 2003, Vargas, Restrepo et al 2011, Vargas, Quiroga et al 2012 or by Shack-Hartmann sensors (Vargas, González-Fernandez et al 2010, Vargas, Restrepo et al 2012). This transformation is not new in cryo-EM as it has been proposed previously to facilitate particle screening (Vargas, Abrishami et al 2013), CTF estimation (Vargas, Oton et al 2013) and local and directional resolution determination (Vilas, Gomez-Blanco et al 2018, Vilas, Tagare et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Then the quality of the reconstructed image is degraded when the inaccurate hologram is used for image reconstruction. Although the technique for expanding the dynamic-range of the recorded interference pattern by using high dynamic-range (HDR) imaging was reported in the field of interferometry [4], any applications of HDR imaging to the digital holography has not been reported yet. In these circumstances, we proposed high dynamic-range digital holography (HDRDH), which expands the dynamic range of a hologram by applying HDR imaging to multiple holograms exposed under different recording conditions, and we numerically confirmed that the HDRDH reconstructs a higher-quality image from the HDR hologram [5].…”
Section: Introductionmentioning
confidence: 99%